3D imaging of the crust and upper mantle beneath the Arctic Ocean from Rayleigh‐wave group‐velocity analysis. (26th January 2018) - Corchete, V.
Abstract : A 3D S‐velocity model for the crust and upper mantle beneath the Arctic Ocean is determined from the analysis of fundamental‐mode Rayleigh‐wave group velocity. This new model allows the characterization of the principal features present beneath the Arctic Ocean, in terms of S‐velocity, for a depth range from 0 to 400 km. In the depth range from 0 to 5 km, the basins with thicker sediments are imaged by the lowest S‐velocity values (2.2–2.3 km/s), whereas the highest S‐velocity values (3.2–3.3 km/s) are associated with a thin sedimentary cover. In the depth range from 5 to 10 km, the lowest S‐velocity values (2.6–2.7 km/s) are also shown in areas with a thick sedimentary cover (>10 km). The higher S‐velocity values (4.0–4.2 km/s) are associated with the areas in which the Moho depth is overcome. In the depth range from 10 to 35 km, also the S‐velocity values are higher (>4 km/s) for the zones in which the Moho depth is overcome. The S‐velocities determined in this study allows to consider the Alpha‐Mendeleev Ridge (formed by the Alpha Ridge and the Mendeleev Ridge) as a continuous feature, because the Alpha Ridge and the Mendeleev Ridge are characterized by similar S‐velocities (e.g., ~3.6 km/s for depths from 10 to 15 km). This region also can be considered as an oceanic large igneous province, in terms of S‐velocity, because the determined S‐velocity pattern is characteristic of these oceanic regions. In general, for the lithosphere (from 35 to 180 km depth), the S‐velocity can be easily correlated with the different age of the Arctic Ocean regions and with the surface tectonic features, whereas for the asthenosphere and the mantle below it (from 180 to 400 km depth), this correlation is not clear. In general, a small S‐velocity contrast (0.1–0.2 km/s) is found between the lithosphere and asthenosphere, which makes it difficult to determine this boundary. Opposite to this, the high S‐velocity contrast (0.4–0.5 km/s) found at the asthenosphere base allows the easy determination of this boundary.